The deaf’s e-learning challenges during COVID-19: Moroccan case study - Ahmed Jadir (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: The lockdown that followed the outbreak of the COVID-19 pandemic necessitated implementing several emergency measures, including some in the realms of education and social services. Classes at all schools have been canceled and replaced by online instruction. Health and protection decisions have also resulted from the pandemic, significantly affecting many people’s lives, especially those with particular requirements. By adapting and improving their innovative methods, Association Marocaine pour Enfants Sourds (AMES) provided effective remote instructions. In this paper, we look into how deaf students in Morocco coped with online education during the country’s 2011 lockdown. Methodology: The challenges and communication barriers that deaf students in Morocco face are first examined and discussed. After that, we look into why, unlike most deaf schools around the world, AMES shut its doors on its deaf students and left them out. We used a qualitative and quantitative approach by conducting a survey and a thematic analysis of the results. Findings: Issues with education, communication, digital illiteracy, and e-learning absenteeism were all highlighted in this research. After that, some suggestions are made. Implications/Novel Contribution: The challenges faced by deaf students in Morocco as they transitioned to online education during the pandemic are investigated in this study. In Morocco, where COVID-19 has had a significant impact, e-learning is still in its infancy compared to other countries.